A Strategy for Reasoning with Close Knowledge Bases : Application to Knowledge Bases on SMEs - Renaud, Dominique; Zanni-Merk, Cecilia; Bouché, Philippe; Gartiser, Nathalie; Rousselot, François (Strategia wnioskowania w heterogenicznych bazach wiedzy : zastosowanie w bazach wiedzy małych i średnich przedsiębiorstw, 2010)
One of the major difficulties encountered when building a real system for handling heterogeneous knowledge bases (KB) with close topics is to combine them without sacrificing the specificity of their contents. The resolution of this difficulty raises some issues about combining multiple ontologies. The largest part of these issues is directly related to the existing mismatches among KBs with close contents. This paper describes a system that uses a compound strategy for minimizing the number of cases of mismatch in the aggregation of close and heterogeneous knowledge. This work is conducted in the context of the MAEOS project about the modeling of the support to the organizational and strategic development of small and medium enterprises (SMEs).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 25-33
Keywords: knowledge bases; ontologies; multi-agent systems; integration of ontologies